Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Harga Terhadap Loyalitas Konsumen Bisnis Pada PT. Mesari Adi Harsa Di Badung (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
High-quality products will influence business consumer loyalty. Service quality is a good marketing strategy to meet the needs of business consumers. Good quality will build business consumer loyalty, which will result in business consumers' desire to continue purchasing the company's products or services. In addition to product quality and service quality, loyalty in business consumers is also achieved by providing appropriate prices. The purpose of this study was to analyze the influence of product quality, service quality, and price on business consumer loyalty at PT. Mesari Adi Harsa in Badung. This research was conducted using quantitative methods. The results showed that product quality, service quality, and price had a positive and significant effect, both partially and simultaneously, on business consumer loyalty at PT. Mesari Adi Harsa in Badung. These findings emphasize the importance for companies to maintain product quality, improve service quality, and implement appropriate pricing strategies to build and maintain consumer loyalty.